Navigating Academic Texts: Challenges and Strategies of International Students in Reading Comprehension - Rahayu, Josilia Puspito; Baehaqi, Luqman; Widiastuty, Hesty (Universitas Gadjah Mada, 2025)
Reading comprehension is a fundamental skill essential for academic success. However, many international students, particularly those from non-English-speaking backgrounds, face significant challenges in understanding academic texts. This study explored the reading comprehension challenges encountered by four Asian international students from Bangladesh, Indonesia, Taiwan, and Vietnam at an American university in New York during the Fall Semester of 2023. It explored the Problem-Solving Strategies they used to overcome these challenges. Using a qualitative phenomenological approach, data were gathered through semi-structured interviews and open-ended questionnaires. The findings revealed that linguistic factors, such as limited academic vocabulary, and non-linguistic factors, such as background knowledge, significantly affect students' reading comprehension. Despite these challenges, students frequently utilized Problem-Solving Strategies, including rereading, adjusting reading speed, and inferring meanings from context, to enhance their understanding. The study highlighted the crucial role of these strategies and suggested that targeted instruction in Problem-Solving Strategies could further support international students' academic success.